2015
DOI: 10.1123/jis.2014-0120
|View full text |Cite
|
Sign up to set email alerts
|

“I’m Running so You Can Be Happy and I Can Keep My Scholarship”: A Comparative Study of Black Male College Athletes’ Experiences with Role Conflict

Abstract: The purpose of this study was to examine the experiences of two groups of Black male college athletes at a Division I historically White institution (HWI) to better understand the key contributors that influenced their academic performance levels, academic engagement, and the quality of their overall college experiences. Two focus groups were conducted with 10 Black male college athletes enrolled at a Division I HWI and a demographic questionnaire was administered to ascertain a better understanding of their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 18 publications
0
34
0
Order By: Relevance
“…Prior research indicates that organizational context-including athletic department culture, relationships with coaches, and academic advising-has implications for student-athlete development (Andrassy, Svensson, Bruening, Huml, & Chung, 2014;Paule & Gilson, 2010). Regarding context and identity more specifically, Cooper and Cooper (2015) found that Black male student-athletes' academic disengagement and identity conflict was shaped by peers and (a lack of) reinforcement around academic accomplishments, among other factors.…”
Section: Situations Of Identity Salience and Conflictmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior research indicates that organizational context-including athletic department culture, relationships with coaches, and academic advising-has implications for student-athlete development (Andrassy, Svensson, Bruening, Huml, & Chung, 2014;Paule & Gilson, 2010). Regarding context and identity more specifically, Cooper and Cooper (2015) found that Black male student-athletes' academic disengagement and identity conflict was shaped by peers and (a lack of) reinforcement around academic accomplishments, among other factors.…”
Section: Situations Of Identity Salience and Conflictmentioning
confidence: 99%
“…That is, the individual conceives of two or more identities as being "constructed so differently in terms of thoughts, feelings, and traits associated with each that they are irreconcilable" (Killeya- Jones, 2005, p. 169). Identity conflict surfaces when the demands of one or more roles make it difficult for an individual to meet the responsibilities of another role (Cooper & Cooper, 2015;Frone, 2000).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach takes an anti-deficit perspective to empower this population (Cooper, 2016). The approach was influenced by various existing frameworks, including Comeaux and Harrison's (2011) conceptual model, Tinto's (1993) theory of student departure, CRT, and strategic responsiveness to interest convergence (SRIC; Cooper & Cooper, 2015). EBA consists of six holistic developmental principles: self-identity awareness, positive social engagement, active mentorship, academic achievement, career aspirations, and balanced time management.…”
Section: Excellence Beyond Athleticsmentioning
confidence: 99%
“…For example, Cooper (2016) noted how institutions often over emphasize Black male student athletes' athletic identities, leading to limited identity integration and exploration. Additionally, sport can afford opportunities to Black athletes who might not otherwise have access to education and economic mobility, making sport performance of even greater import (Cooper & Cooper, 2015). Given these trends, it is understandable that many Black athletes would endorse heightened levels of athletic identity.…”
Section: Mediation Model With Athletic Identity As the Predictor Varimentioning
confidence: 99%